Analisis Pengaruh Pemberian Dana Pendidikan Bantuan Operasional Sekolah (BOS) Terhadap Angka Partisipasi Kasar (APK) di Kabupaten/Kota Provinsi Jawa Tengah Tahun 2015-2017 - Ririh Tia Rutfiana; Banatul Hayati (Diponegoro Journal of Economics, 2020)
One of the policies taken by the Indonesian government to improve the quality of human resources is through access to education for the whole community through the allocation of education subsidies. The target of the education subsidy program is to increase the Gross Enrollment Rate (GER). This study focuses on analizing the influens of the School Operational Assistance program, education budget, Gross Reguional Domestic Product Percapita and Gross Enrolment Rate of the previous year (GER(-1)) at the Elementary School, Junior High School dan Senior high School. In Regency/City of Central Java Province in 2015-2017. The research is quantitative analysis using Panel Fixed Effect Model (FEM) data estimation. Research results show that at the Elementary School level education budget and GER (-1) have a positive and significant effect on GER. At the Junior High School level, Gross Reguional Domestic Product Percapita and GER (-1) has positive significant impact to GER.At Senior High School level, School Operational Assistance program, education budget and Gross Regional Domestic Product percapita has positive significant impact to GER.